(untitled) (International Journal of Occupational Safety and Health, 2025)
Introduction: Nipah leaf crafters regularly perform tasks involving awkward postures—such as sitting on the floor without back support—repetitive hand movements, manual handling of Nipah leaves and sticks, and working in a physically uncomfortable environment. These factors present potential ergonomic hazards that can lead to musculoskeletal disorders (MSDs), often manifesting as pain in various body parts. This study aimed to identify potential ergonomic hazards and the presence of MSDs, as well as to analyze their relationship. Methods: This quantitative study employed a cross-sectional design and involved 35 Nipah leaf crafters. Potential ergonomic hazards were measured using a standardized checklist, and musculoskeletal disorders were assessed using a survey based on Appendices D and B of the Indonesian National Standard (SNI) 9011:2021. The research utilized univariate and bivariate methods, and relationship between ergonomic risks and musculoskeletal outcomes was analyzed using analysis of variance (ANOVA). Results: Common ergonomic hazards identified included awkward postures, repetitive motion, lifting, poor lighting, and exposure to solar heat. Twenty-two participants (62.90%) were classified as "requiring further observation." Reports of MSDs varied in frequency and severity across body regions, with 21 individuals (60.00%) categorized as low-risk. A statistically significant relationship (p < 0.05) was found between potential ergonomic hazards and the incidence of MSDs. Conclusion: This study highlights the urgent need to address occupational health risks among Nipah leaf crafters to prevent MSDs, promote worker health, and improve productivity.